Karakterisasi Jamur Patogen Penyebab Penyakit Pada Tanaman Srikaya (Annona Squamosa) di UD. Sabila Farm: Karakterisasi Jamur Patogen Penyebab Penyakit Pada Tanaman Srikaya (Annona Squamosa) di UD. Sabila Farm - Purnomo, Azis; Pratama, Dion; Bintang Pamungkas, Puguh; Kandito, Argawi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2025)
Soursop (Annona squamosa) is a horticultural crop with high economic value. However, this plant is susceptible to diseases caused by pathogenic fungal infections, which can reduce yield and fruit quality. This study aims to identify pathogenic fungi affecting soursop plants at UD. Sabila Farm and understand their role in disease development. The research was conducted at UD. Sabila Farm, located in Kapanewon Pakem, Sleman Regency, Special Region of Yogyakarta. Further laboratory analyses were carried out at the Biology Laboratory, Faculty of Agriculture, Universitas PGRI Yogyakarta. The study employed field exploration and laboratory identification using Potato Dextrose Agar (PDA), samples were collected from leaves, stems, and fruits showing signs of infection. The findings revealed several fungal pathogens contributing to plant diseases, such as Colletotrichum sp., Fusarium solani sp., and Curvularia sp.. Morphological characterization and pathogenicity analysis provide a foundation for developing effective disease management strategies. This research is expected to support farmers in maintaining plant health and improving soursop production sustainably.